Food and feeding habits of wildfowl - Olney, P J S (Wildfowl, 1957)
At the present time detailed information on the food of the British wildfowl is extremely meagre. It is fair to say that much of the existing information is not only valueless but is often misleading, either because it records an unusual food or feeding habit or, and this is the most common error, it is too vague. It is not enough to know that for a particular species pond weeds or grain and grass are part of the normal diet. Identification must be more precise.